Reproductive biology of several garcinia species of agricultural importance in Malaysia - Emlee, Aiesyaa Majdiena; Rohani, Emelda Rosselena; Mohd Noor, Normah; Midin, Mohd Razik (Universiti Putra Malaysia Press, 2025)
The Garcinia genus belongs to the Clusiaceae or Guttiferae family, comprising 350 species. Garcinia is a large genus, and it is widely distributed in tropical environments, especially in the Southeast Asia region. Despite their wide distribution in Malaysia, information on their reproductive biology is still lacking. This overview highlights the distribution and the reproductive system of several Garcinia species in Malaysia, which are Garcinia mangostana var. mangostana, Garcinia celebica, Garcinia mangostana var. malaccensis, Garcinia prainiana, Garcinia cowa, Garcinia atroviridis and Garcinia parvifolia. Apomixis, specifically agamospermy in Garcinia species, is widely acknowledged by previous research. Apomixis develops a distinctive mechanism in gametophytic and sporophytic types, and it is molecularly triggered either by hybridisation or polyploidisation. G. mangostana var. mangostana is classified under obligate apomict due to male sterility caused by the alteration of tapetum during pollen development. On the other hand, the occurrence of male trees, male fertility and pollen viability are the important features that consider G. celebica, G. mangostana var. malaccensis, G. prainiana, G. cowa, G. atroviridis and G. parvifolia to be facultative apomict. Besides, the seeds of Garcinia species are recalcitrant and possess low resistance to desiccation. The size and moisture content of the seeds can influence germination ability. The overall information of this review can help explore the life cycle of Garcinia trees to facilitate conservation programs along with the agricultural benefits.